Evaluating the use of the branched‐chain amino acids in combination with urea on creeping bentgrass at establishment. Issue 1 (24th February 2021) - Mertz, Isaac; Thoms, Adam; Christians, Nick
Abstract: The branched‐chain amino acids (BCAA) leucine (L), isoleucine (IL), and valine (V) are synthesized in plants and essential to growth in most organisms. Research has shown that when foliarly applied, these compounds can be absorbed by the plant, however, plant catabolism of BCAA is not completely understood. A ratio of 4:1:1 (L:IL:V) applied at 3.4 kg‐nitrogen (N) ha −1 was identified as the optimal application ratio for increasing creeping bentgrass ( Agrostis stolonifera L.) shoot density, however, material incompatibility issues occurred when BCAA were applied at 8:1:1 and 12:1:1 in previous work. The objective of this study was to determine if shoot density could be further increased by using lower BCAA ratio rates in combination with urea and GreenNCrease to equalize N at establishment. Creeping bentgrass samples grown in sand‐filled pots were subjected to N application (3.4 kg‐N ha −1 application −1 ) using urea, GreenNCrease, BCAA 4:1:1, 8:1:1 and 12:1:1. The BCAA were also applied as 4:1:1+N, 8:1:1+N, and 12:1:1+N, which consisted of BCAA half‐rates (1.7 kg‐N ha −1 ) and urea‐N (1.7 kg‐N ha −1 ). At the end of the study, material incompatibility previously observed with 8:1:1 and 12:1:1 was alleviated through use of the BCAA half‐rates, however, 4:1:1 and 4:1:1+N led to a greater root weight compared to urea alone. After 10‐weeks, BCAA 4:1:1 and 4:1:1+N, increased shoot density by 54% and 49%, respectively, compared to equal urea N. This very low rate of nitrogen supplied by the urea applications was not enough to elicit the typical growth response that is seen from urea at higher levels. According to these results from creeping bentgrass grown in pots, using BCAA 4:1:1, either as a standalone N application or tank mixed with urea as a portion of the total applied N, will lead to best increases in shoot density and root weight compared to equal urea N.